Prevalence of dental caries in pediatric patients with atopic dermatitis - T.M. Volosovets; I.G. Dikova; O.V. Mozyrska; N.A. Slyusar (Zaslavsky O.Yu., 2023)
Background. Children with atopic dermatitis may be at increased risk of developing dental caries. This problem is poorly understood and needs attention. The aim of this study was to investigate the oral health status of children and adolescents with atopic dermatitis. Materials and methods. One hundred children with atopic dermatitis aged 2 to 17 years, median of 6 [3.5; 10], and 103 children without atopic dermatitis, median age 7 [5; 12.5] years, were included in the study. Clinical parameters included age, sex, age of onset and severity of atopic dermatitis according to the SCORing AD index (SCORAD). Patients with at least one type of caries at any stage of progression (from white spots to carious lesions with pulpal damage) were included in the caries group. The risk of caries in the atopic dermatitis group and in healthy children, and the significance of the presence of asthma and allergic rhinitis for the development of caries were evaluated using the odds ratio (OR) with a 95% confidence interval (CI). Results were considered statistically significant at the p < 0.05 level. Results. Caries was detected in 46 % of children with atopic dermatitis and 22 % controls (OR = 2.9630, CI 1.6131-5.4424, p = 0.0005). In the group of allergic rhinitis, 24 patients were found to have caries, and among those without allergic rhinitis, 22 children had caries. It was found that patients with concomitant allergic rhinitis were significantly more likely to develop caries (OR = 3.4406, CI 1.4693-8.0563, p = 0.0044). No such significance was found depending on the presence of asthma (OR = 1.3986, CI 0.4913-3.9814, p = 0.5). Conclusions. Children with atopic dermatitis have a significantly higher risk of dental caries than healthy children. Based on the results of our study, clinicians should be aware of dental manifestations in patients with atopic dermatitis and recommend regular dental examinations for early caries detection.